A systematic review and meta-analysis on different stem fixation methods of radial head prostheses during long-term follow-up - Yang, Guang; Li, Shangzhe; Zhang, Hailong; Lu, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Radial head arthroplasty (RHA) is typically performed for non-reconstructible radial head fractures with or without valgus stability. The fixation methods can be divided into cemented rigid fixation, such as screw fixation, and uncemented micromovement fixation, including smooth stem, press-fit, expanded device, in-growth stem, and grit-blasted stem fixations. Different fixation methods may impact long-term clinical outcomes and cause complications. This study aimed to compare the long-term follow-up outcomes of cemented and uncemented radial head prosthesis. Methods: A computerized literature search was performed in the PubMed/MEDLINE, Embase, Cochrane Library, and Web of Science databases for studies on radial head prosthesis, replacement, and arthroplasty published from inception to April 2022. The prosthesis fixation method was divided into cemented and uncemented fixation groups. The outcomes of interest included the participant characteristics, prosthesis types, clinical outcomes, reoperation rates, and complication rates during long-term follow-up. Results: A total of 57 studies involving 2050 patients who underwent RHA were included in our analysis. Cemented fixation was used in 23 of these studies, uncemented fixation in 35, and both cemented and uncemented fixations in 1. Both fixation groups showed significantly improved clinical outcomes after treatment. In particular, both the reoperation and complication rates were lower in the uncemented fixation group (12% and 22%, respectively) than that in the cemented fixation group (20% and 29%, respectively). Among the studies, uncemented monopolar fixation had the lowest reoperation rate (14%), while cemented monopolar fixation had the highest reoperation rate (36%). Regarding complications, uncemented bipolar fixation yielded the lowest rate (12%), while cemented bipolar fixation yielded the highest rate (34%). The ranges of motion and clinical outcome scores were good in both groups. Conclusions: Uncemented radial head prosthesis are associated with lower reoperation and overall complication rates than cemented prosthesis. In particular, uncemented monopolar prosthesis may yield the lowest reoperation rate, while uncemented bipolar prosthesis may yield the lowest overall complication rate.